Analytic and Integrative Framework for Understanding Human Sympathetic Arterial Baroreflex Function: Equilibrium Diagram of Arterial Pressure and Plasma Norepinephrine Level - Yamasaki, Fumiyasu; Sato, Takayuki; Sato, Kyoko; Diedrich, André (Frontiers in Neuroscience, 2021)
Background The sympathetic arterial baroreflex is a closed-loop feedback system for stabilizing arterial pressure (AP). Identification of unique functions of the closed system in humans is a challenge. Here we propose an analytic and integrative framework for identifying a static operating point and open-loop gain to characterize sympathetic arterial baroreflex in humans. Methods and Results An equilibrium diagram with two crossing functions of mechanoneural (MN) and neuromechanical (NM) arcs was analyzed during graded tilt maneuvers in seven healthy subjects. AP and plasma norepinephrine level (PNE), as a surrogate for sympathetic nerve activity, and were recorded after vagal modulation of heart function was blocked by atropine. The MN-arc curve was described as a locus of operating points during –7, 0, 15, and 60° head-up tilting (HUT) on a PNE-AP plane. The NM-arc curve was drawn as a line between operating points before and after ganglionic blockade (trimethaphan, 0.1 mg⋅ml–1⋅kg–1) during 0° or 15° HUT. Gain values were estimated from the slopes of these functional curves. Finally, an open-loop gain, which is a most important index for performance of arterial baroreflex, was given by a product of the gain values of MN (GMN) and NM arcs (GNM). Gain values of MN was 8.92 ± 3.07 pg⋅ml−1⋅mmHg−1; and GNM at 0° and 15° HUT were 0.61 ± 0.08 and 0.36 ± 0.05 mmHg⋅ml⋅pg–1, respectively. A postural change from supine to 15° HUT significantly reduced the open-loop gain from 5.62 ± 0.98 to 3.75 ± 0.62. The effects of HUT on the NM arc and open-loop gain seemed to be similar to those of blood loss observed in our previous animal studies. Conclusion An equilibrium-diagram analysis contributes to a quantitative and integrative understanding of function of human sympathetic arterial baroreflex.